Rancang Bangun Sistem Multipoint Transmitter – Receiver untuk Inspeksi Bawah Air Berbasis Ultrasonik Frekuensi Rendah - Muhammad Edy Hidayat; Agus Indra Gunawan; Tri Budi Santoso (Jurnal Rekayasa Elektrika, 2020)
Non-destructive testing and evaluation are testing techniques that test and evaluate the properties of a material, component, or system without causing any damage caused by the testing and evaluation process. Ultrasonic sensors are devices with minimal risk in their use and are quite often used in non-destructive testing and evaluation processes. Low frequency ultrasonic (200kHz) has been used in the testing and evaluation process in several scientific fields. Improving the test capability of low-frequency ultrasonic measurement instruments while remaining efficient and affordable is the core of this research. Increasing test capability and efficiency by adding five test points to a low-frequency ultrasonic measurement instrument for underwater inspections have been carried out by engineering a trigger signal generator that transmits 35kHz signals at 50V voltage proven to improve the quality of the echo signal received when compared to using trigger signal sourced directly from the wave generator device, the use of a pre-amplifier module on the receiver side of the echo signal is proven to be able to increase the voltage level of the echo signal and improve the reading value of the received echo signal, as well as the signal coupling mechanism built in this study, proved to be adequate to increase efficiency multipoint testing using one ultrasonicbased testing instrument.